2018
DOI: 10.1002/ana.25213
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus: Role for etiology in determining response to benzodiazepines

Abstract: SE-model-dependent differences support a novel hypothesis that the development of benzodiazepine pharmacoresistance may be etiologically predetermined. Further studies are required to investigate the mechanisms that underlie such etiological differences during SE and whether etiology-dependent protocols for the treatment of SE need to be developed. Ann Neurol 2018;83:830-841.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
(142 reference statements)
1
20
0
Order By: Relevance
“…All the experiments were performed in accordance with the Animal Ethics Committee of Chongqing Children’s Hospital, and all animal procedures were approved by the Laboratory Animal Care Committee of Chongqing Medical University. All rats were housed in a controlled environment (food and water were supplied ad libitum, 21±1°C, humidity 60%, 12-h light/dark cycle) [13]. First, the rats were injected intraperitoneally with lithium chloride (127 mg/kg, i.p., Solarbio, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…All the experiments were performed in accordance with the Animal Ethics Committee of Chongqing Children’s Hospital, and all animal procedures were approved by the Laboratory Animal Care Committee of Chongqing Medical University. All rats were housed in a controlled environment (food and water were supplied ad libitum, 21±1°C, humidity 60%, 12-h light/dark cycle) [13]. First, the rats were injected intraperitoneally with lithium chloride (127 mg/kg, i.p., Solarbio, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In another study, all seizures were terminated when treated after 10 min (3/3), but not after 45 min of SE (0/3) [21]. In contrast, a comparative study of KA-SE and LiPilo-SE in a rat model of SE demonstrated preserved efficacy of BZD after 3 h in the KA-SE model where GABAR surface expression was preserved compared to the LiPilo-SE animals, which developed BZD resistance associated with decreased surface expression of GABAR [27]. These animal models support the development of progressive pharmaco-resistance with longer seizures duration, which may be etiologically-dependent.…”
Section: Animal Modelsmentioning
confidence: 93%
“…Changes in neurotransmitter receptor (NTR) localization may be etiologically dependent. A recent study comparing status epilepticus in rats due to either kainic acid (KA-SE) or lithium-pilocarpine (LiPilo-SE)_demonstrated increased GABA A R internalization in the Li-Pilo-SE model compared to the KA-SE animals, in addition to differential surface expression of Kv4.2 potassium channels [27]. Therefore, internalization of GABA A R may, at least in part, contribute to progressive pharmaco-resistance to BZD during SE [18,[24][25][26] (Fig.…”
Section: Neurotransmitter Receptor Traffickingmentioning
confidence: 99%
“…The threshold of 30 min onward after seizure onset was chosen because it aligns with the classical definition of SE 25 and because responsiveness to BZDs in animal models is markedly lower after that time point 26–28 . However, limited animal and human series with prolonged SE presented complete resolution after a single BZD dose, suggesting a potential involvement of other factors in BZD response besides seizure duration, or the need for longer seizure duration to develop BZD resistance in some cases 29,30 . As responsiveness to BZDs may still be present later, we added an additional threshold of 45 min.…”
Section: Methodsmentioning
confidence: 99%